Analisis Faktor Identification, Shared Language, dan Shared Vision Untuk Penerapan Knowledge Management System Untuk Mahasiswa Perguruan Tinggi di Indonesia - Handrie Noprisson (JSAI (Journal Scientific and Applied Informatics), 2025)
This study aims to analyze the factors influencing Knowledge Sharing in the implementation of the Knowledge Management System (KMS) among university students. The three main variables examined are identification, shared language, and shared vision. Data were collected through online surveys and questionnaire distribution to students from various universities in Indonesia. A total of 420 questionnaires were distributed, and after validation, 400 questionnaires were used for analysis. Data analysis was conducted using SmartPLS version 3.2.7 with the Structural Equation Modeling (SEM) approach. The study results indicate that shared language has a significant influence on knowledge sharing, while identification shows a near-significant effect. Conversely, shared vision does not have a significant impact on knowledge sharing. The validity and reliability values confirm that all variables strongly contribute to the research model. The research implications suggest that a common language understanding plays a crucial role in enhancing knowledge sharing within academic environments